2019
DOI: 10.1002/aocs.12281
|View full text |Cite
|
Sign up to set email alerts
|

A Greener Alternative Titration Method for Measuring Acid Values of Fats, Oils, and Grease

Abstract: A greener alternative method is proposed for measuring acid values (AV) of fats, oils, and grease (FOG) based on visual titration. Compared with Official Method Cd 3d-63 of the American Oil Chemists' Society (AOCS), this greener alternative method can eliminate the use of toluene, which in turn reduces toxicity and cost. A total of 44 samples of yellow and brown grease with AV ranging from 0.13 to 170.37 (mg KOH) g −1 were titrated using both methods. The alternative titration method can provide accurate and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…40 The titration method is a simple and cost-effective way to measure the concentration of FA and triglycerides in a sample. Zhang et al 41 evaluated different titrimetric methods for analyzing FA and acid values in FOG samples, as shown in Table 1. They found that the widely used AOCS Cd 3d-63 method had issues with the use of toluene, which raised toxicity concerns.…”
Section: Analytical Methods For Analysing Fatty Acidsmentioning
confidence: 99%
“…40 The titration method is a simple and cost-effective way to measure the concentration of FA and triglycerides in a sample. Zhang et al 41 evaluated different titrimetric methods for analyzing FA and acid values in FOG samples, as shown in Table 1. They found that the widely used AOCS Cd 3d-63 method had issues with the use of toluene, which raised toxicity concerns.…”
Section: Analytical Methods For Analysing Fatty Acidsmentioning
confidence: 99%
“…ML was synthesized as follows agreeing with the procedure described by Murad et al 22 : (i) heat LA at 44 C to 46 C 33 (ii) add methanol; (iii) heat the mixture until reaching the reaction temperature and add a previously defined amount of sulfuric acid into the reaction mixture (on mass basis taking into account only the LA amount) and then subject the resulting admixture to HSM for the reaction for a given period of time (mixing was done with a ROSS HSM-100 LCI high shear mixer with a slotted stator head dispersion attachment), (iv) eliminate the excess of methanol at reduced pressure, (v) place the methanolfree sample in a separation funnel to split the aqueous fraction (water and sulfuric acid) from the unconverted LA and the formed ML and (vi) titrate the methanol, water and sulfuric acid-free LA and ML mixture with a solution of potassium hydroxide with the aim to neutralize and quantify the remaining LA. The acid value (AV) measurement was conducted according to the method described by Zhang et al 34 The AV was quantified by applying Equation (1), wherein A corresponds to the milliliters of potassium hydroxide solution employed in the titration, B is the solution required for blank solvent titration, C denotes the molarity of the potassium hydroxide solution, 56.1 corresponds to the molecular mass of potassium hydroxide and M is the mass of titration.…”
Section: La Reactionmentioning
confidence: 99%
“…Manketti nut oil is tested for free fatty acid content (FFAs) using conventional AOCS (American Oil Chemists' Society) titrimetric method as described elsewhere [14,15]. The manketti nut oil recorded FFAs of about 1.85%, which is below the recommended upper limit of 2%.…”
Section: Biodiesel Productionmentioning
confidence: 99%